2015
DOI: 10.1097/gme.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and postmenopausal hormone therapy in Spain

Abstract: In this Spanish population, several demographic, lifestyle, occupational, and reproductive factors are associated with use of hormonal compounds. Characterizing hormonal users and monitoring trends in the use of these hormonal compounds are essential from a public health perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
4
19
1
Order By: Relevance
“…Other studies published in Spain estimated a prevalence ranging from 3% to 10%. 4,17,[29][30][31][32] Regarding the prevalence of HT by age, our study demonstrated that a higher percentage of younger women were current users-a finding that is consistent with what was observed in the majority of the European countries. 33 However, the opposite was true in the United States, where women aged 60 to 69 years are the group with higher prevalence.…”
Section: Isidoro Et Alsupporting
confidence: 93%
“…Other studies published in Spain estimated a prevalence ranging from 3% to 10%. 4,17,[29][30][31][32] Regarding the prevalence of HT by age, our study demonstrated that a higher percentage of younger women were current users-a finding that is consistent with what was observed in the majority of the European countries. 33 However, the opposite was true in the United States, where women aged 60 to 69 years are the group with higher prevalence.…”
Section: Isidoro Et Alsupporting
confidence: 93%
“…BMI may predict menopausal symptoms, and a high current BMI may indicate a lower need for HT around menopause [49]. However, the weak correlation between baseline BMI and HT use in our study suggests that the two factors may be regarded as independent.…”
Section: Discussioncontrasting
confidence: 58%
“…We also assessed if these associations differ by specific CRC subsite. Finally, taking into account that reproductive patterns and the use of hormonal compounds are strongly influenced by womens’ educational level [ 13 ] and that highly educated women tend to have healthier life-styles [ 14 , 15 ], we evaluated the influence of reproductive factors separately in women with high and low educational background.…”
Section: Introductionmentioning
confidence: 99%